Laying the Groundwork for a CEFR-Referenced English Proficiency Test with Vocational Nuance at Politeknik Negeri Jember - Taufan, Gullit Tornado; Pramudita, Rizqi Febrian; Rahmanita, Meiga; Rachman, Nur Afni; Putri, Astrid Hidayanti Ananda (P3M Politeknik Negeri Jember, 2025)
English language proficiency tests have become an integral part of English language learning. Several standardized English proficiency tests are offered to test takers for various purposes. TOEFL, IELTS and TOEIC are those that are widely recognized internationally. Standardized English tests have also been developed by institutions in Indonesia, such as TAEP by the University of Muhammadiyah Malang and TOEP (PKBI) by the Indonesian Test Service Center (PLTI). However, to date, there are still no similar tests administered by institutions in Indonesia specifically designed for vocational contexts. Therefore, this study was conducted to analyze the needs of developing a blueprint for the English proficiency test of Jember State Polytechnic (Polije) with a vocational nuance referring to the Common European Framework of Reference. Data were obtained through interviews with the Head of the Language Center of Polije, analysis of existing documents of the test blueprint and samples, analysis of the development of departments at Polije for the consideration of the vocational aspects, and analysis of the CEFR which will serve as the reference of the blueprint. The results of the data analysis will serve as the basis for developing a blueprint for the Polije English proficiency test with a vocational nuance referring to the CEFR.